Mathematical Modeling of Blood Flow With the Suspension of Nanoparticles Through a Tapered Artery With a Blood Clot - Shah, Sapna Ratan; Kumar, Rohit (Frontiers in Nanotechnology, 2020)
In this study, some key new developments in nanoscience which highlight the problem of nanoparticles in blood flow through mild stenosis in the presence of a blood clot have been presented. The blood flow behavior through the stenosed artery is considered using the Prandlt fluid model and the flow of blood is considered as suspension of nanoparticles. An appropriate non-linear system of equations governing blood flow is represented in a cylindrical coordinate system and solved exactly under mild stenotic conditions using the geometry of the stenotic artery in the presence of a clot. Heat transfer phenomena have been examined for the physical features of the flow of blood through a stenosed artery, which is tapered in shape and with the presence of a clot. The temperature profile has been discussed with graphs for several different parameters of clot size, stenosis height, heat source, and sink parameter. Tapering phenomena has been analyzed for temperature profile. It is examined that in converging tapering the temperature provides greater values as estimated together with the non-tapered arteries and diverging tapering arteries. In this work, it is also analyzed that with a rise in the clot size (σ) the temperature (θ) increases, whereas the radius of the artery with stenosis h(z) decreases and heat source and sink parameter (D) increases.